Learning English Vocabulary By Lingodeer: Case Study of Indonesian Junior High School Students - Triwiyanti, Icha; Ahmad Amin Dalimunte (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study explores the implementation of the Lingodeer application as a medium for improving students' vocabulary at a Private Islamic Junior High School in Medan, Indonesia. Using a qualitative approach, data were collected through questionnaires and student interviews. Lingodeer was selected due to its interactive design, accessibility, and focus on grammar and vocabulary, essential components in language acquisition. The results show that students became more enthusiastic, engaged, and motivated when learning vocabulary through the app. They reported improved vocabulary recall, pronunciation, and interest in English lessons. However, several challenges were noted. Some students faced difficulties pronouncing unfamiliar words, and the app's premium version was considered expensive, with limited variety in its gamification features and supplementary content. Despite these limitations, the findings suggest that Lingodeer is an effective and enjoyable tool for enhancing students' English vocabulary. It offers valuable support for language teachers seeking engaging alternatives to traditional instruction.